Food security in the South Pacific Island countries with special reference to the Fiji Islands - K. L. Sharma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper analyses the status of food security in selected South Pacific Island countries, namely Cook Islands, Fiji Islands, Papua New Guinea, Samoa, Solomon Islands, Tonga, and Vanuatu at the national and household levels during the period 1991-2002. Due to narrow resource base and production conditions, Pacific Islands concentrate on a few primary commodities for production and exports. During recent years import dependency for food items has increased mainly due to a decline in per capita food production and a rapid rate of rural-urban migration. Currently, export earnings can finance food imports but earnings could fall short of the requirements needed after the expiry of some commodity preferential price agreements with importing countries. National food security is dependent on the continuation of subsistence farming and tapping ocean resources in conjunction with the on-going commercial farming of those crops in which Pacific Islands have a comparative advantage. Increased productivity is crucial for improving agricultural performance through government investment in rural infrastructure, agricultural research and extension, irrigation and appropriate price incentives. This would also help alleviate poverty for improvement in economic accessibility of food by households. There is also a need to design appropriate disaster risk management programmes to minimize any adverse effects on the food supply.
Keywords: I31; Q18; O15; 330; food security; Pacific Island countries; trade; self-reliance; Nahrungsmittelversorgung; Südpazifischer Inselraum